Pengaruh Komposisi Kimia dan Sifat Reologi Tepung Terigu terhadap Mutu Roti Manis - Feri Kusnandar; Harya Danniswara; Agus Sutriyono (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Wheat flour is the main ingredient in bread processing. Wheat flour manufacturers produce quality wheat flour suitable for bread in term of its chemical composition and rheological properties. This study compared four types of wheat flours (premium high protein, high protein, economic high protein, and medium protein) produced by PT XYZ (namely GC, GE, KR and BS) with wheat flours produced by other manufacturers (TTK1 to TTK8) in the making of sweet bread. Chemical composition (moisture, ash, protein and gluten), Farinograph profile and sensory quality of the resulting sweet bread were compared. The quality of GC flour had a high moisture and lower protein content than wheat flours in the same class (TTK1, TTK2). This affected the rheological characteristics, i.e a low development time and stability, as well as a high mixing tolerance index (MTI). The KR flour had a higher ash content than other flours in the same class (TTK5, TTK6), while BS flour had a higher moisture content than TTK7 and TTK8. The moisture content of wheat flour had negative correlations on sweet bread taste, while the ash had negative correlations on aroma, crumb, and taste. The protein and gluten of wheat flour affected its rheological characteristics, hence contributed to volume, crumb and softness of sweet bread.